The dynamics of the nursing process - T.G. Mashaba (AOSIS, 1981)
THE nursing process is a scientific method of approaching and planning the nursing care of the patient. It is an ongoing process and has a different meaning for each patient at different stages of his illness. It also varies from one nurse to another and at different levels of a nurse's professional maturity and in different nursing situations.